Desain Real-Time Monitoring Berbasis Wireless Sensor Network Upaya Mitigasi Bencana Erupsi Gunungapi - Johan Pamungkas; Wirawan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Geological layout contributes Indonesia in becoming one of the most dangerous countries with natural disasters. The eruption of volcano is one of the most dangerous natural disasters in the world. However, our efforts in disaster mitigation is not enough, especially in developing new mitigation technology. We already know that the Wireless Sensor Network (WSN) technology can be an alternative electronic communications technology that can be used in disaster mitigation because the WSN has the ability to communicate using Radio Frequency (RF) and can be connected to a digital or analog sensor. Then, the Computer Personal Unit (CPU) in WSN is used to run the protocols, such as hop-to-hop protocols. Later, we can build a monitoring system that have small size, energy saving, low cost, and capable to show real-time monitoring. The problem that must be solved in this research is how to make a design communication based on WSN that have accordance with the extreme conditions like at Kelud Volcano. Currently, with utilization of temperature sensor and gas sensor and delivery schedule of data packets as parameters, we want to find how to test the design with minimal electricity supply.